MAGNETIC RESONANCE IMAGING IN DIAGNOSING FIBROTIC AND CICATRICIAL HEART ALTERATIONS IN CHILDREN - L. S. Namazova-Baranova; V. I. Barskiy; V. E. Sinitsyn; E. N. Basargina; A. N. Getman; A. B. Sugak; I. V. Silnova; E. N. Arkhipova; A. K. Gevorkyan (Union of pediatricians of Russia, 2014)
The article provides an analysis of capabilities of magnetic resonance imaging with delayed contrast enhancement in diagnosing fibrotic alterations of varying severity. A hyperintense signal in the setting of myocardial delayed contrast enhancement programs indicates alterations of myocardial structure. Localization, severity and hyperintense signal size facilitate correct diagnosis and prognosis of complications development.